Routine antenatal molecular testing for α-thalassemia at a tertiary referral hospital in China: ten years of experience - Li, Dongming; Liang, Lifang; Meng, Dahua; He, Sheng (Frontiers in Genetics, 2024)
Objective: This study aimed to evaluate the efficacy of α-thalassemia gene testing as a part of an antenatal intervention program over a 10-year period.Methods: All patients underwent α-thalassemia gene testing, which included the analysis of three types of deletions and mutations. Rare α-thalassemia gene testing was performed using Sanger sequencing, multiplex ligation-dependent probe amplification, and sequencing techniques. Prenatal diagnosis was performed in high-risk couples using chorionic villus sampling or amniocentesis.Results: From 2010 to 2019, among the 91,852 patients examined, α-thalassemia mutations were identified in 41.78% of patients. The most frequent α 0 gene mutation was --SEA , followed by --THAI .Two rare α 0 -thalassemia gene mutations at --32.8 and --230 , were also observed. A total of 2,235 highrisk couples were identified, of which 562 were affected, including three with the --SEA /--THAI genotype and one with the --SEA /--230 genotype. Additionally, prenatal diagnosis revealed four cases of fetal anemia and/or mild edema, along with two cases of severe fetal edema. Chromosome and gene chip results were normal. Thalassemia gene testing showed an α CS α/α CS α genotype in four patients with anemia and/or mild edema, while two patients with severe fetal edema had one --SEA /α CS α genotype and one --SEA /--GX genotype. Using the cut-off points of 74.6 fL and 24.4 pg as criteria for identifying α 0 -thalassemia carriers and HbH disease, the detection rate of missed diagnoses in high-risk couples is consistent with national guidelines for standards, potentially saving 10,217,700 ¥.Routine molecular testing for α-thalassemia in high-risk prenatal populations effectively prevented severe α-thalassemia births. Despite the high cost, the cutoff points proposed by this study suggest that implementing screening using a new parameter has the potential to reduce current expenses.